1997
DOI: 10.1093/rheumatology/36.11.1214
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile chronic arthritis: diagnosis and management of tibio-talar and sub-talar disease

Abstract: The aim of this study was to compare clinical evaluation of the site of hindfoot synovitis with contrast-enhanced magnetic resonance imaging (MRI) findings in children with juvenile chronic arthritis (JCA), and to evaluate the efficacy of selective guided intra-articular steroid injections. Thirteen symptomatic ankles of 11 consecutive JCA patients were examined clinically and with contrast-enhanced MRI. Pannus was demonstrated on MRI in both tibio-talar and sub-talar joints in 10 ankles, in the tibio-talar jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 6 publications
2
50
0
Order By: Relevance
“…Moreover, the presence of inflammatory signs (synovitis or effusion) seems to correlate with the degree of improvement (22). An improved outcome after the use of magnetic resonance imaging to show synovitis in the subtalar joint, and after injection into both tibiotalar and subtalar joints using radiographic guidance, was demonstrated in children (23).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the presence of inflammatory signs (synovitis or effusion) seems to correlate with the degree of improvement (22). An improved outcome after the use of magnetic resonance imaging to show synovitis in the subtalar joint, and after injection into both tibiotalar and subtalar joints using radiographic guidance, was demonstrated in children (23).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that injections performed using imaging guidance (fluoroscopy, ultrasound, or CT) more accurately deliver the medications to the desired target joint compared to injections using palpation alone [1,[3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The posterior subtalar joint is one of the most typically injected foot articulations [10][11][12][13][14][15]. There are various techniques described in the literature for injecting medication into this joint, including the anterolateral, posteromedial, lateral oblique, and posterolateral approaches [10][11][12][13]15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations